Curriculum management competency of Malaysia’s principals - Alias, Bity Salwana; Zainudin, Zaida Nor; Mohamad Nasri, Nurfaradilla (Human Resource Management Academic Research Society, 2018)
Previous studies show that there are still issues of Malaysia principal competency in managing curriculum. Therefore the purpose of this study is to identify how far this statement is true and to recommend the best solution in handling this issue. The definition of competency in this study is the level of knowledge and skill that principals have in managing curriculum. To get the data, questionnaires has been sent to 314 principals, 720 senior assistants, and 611 senior teachers from all over Malaysia. Findings show that based on principals self evaluation and their subordinates evaluation, overall, principals competency in managing curriculum is at a high level with a mean score 4.30. Principals self evaluation also show that their knowledge to plan strategies to improve curriculum achievement is at a very high level but their skills to ensure teachers give priority to teaching and learning, to ensure curriculum change that is fully implemented, to encourage cooperation among teachers in implementing teaching and learning, and to mobilize effective programs are still at a medium level. Based on these findings, this study recommends that all principals must attend leadership training before being appointed as principals.